Constructing molecular polygons using halogen bonding and bifurcated N-oxides - Aakeröy, Christer B.; Wijethunga, Tharanga K.; Desper, John (My University, 2013)
Bifurcated halogen bonds constructed from N-oxides and complementary halogen-bond donors provide the basis for a synthetic strategy for the deliberate assembly of molecular polygons in the solid state. The donor- and acceptor sites were located on different molecular components and a co-crystallization approach furnished the desired architectures.
Keywords: Molecular polygons; Halogen bonding; Bifurcated halogen bonds; N-oxides